The Scale of Online Course Anxiety: Assessing College Students’ Anxiety in Online Courses - Li, Xinyang; Lan, William; Williams, Amanda (Online Learning, 2021)
The purpose of this study was to develop an instrument to measure student online course anxiety, a factor that detrimentally affects student learning in the online environment. Based on Keegan’s theoretical framework that identified fundamental differences between online education and traditional education, the instrument of Scale of Online Course Anxiety (SOCA) was developed and tested with a sample of 170 students from a 4-year higher educational institution. The total score and the four subscale scores show high reliability. Confirmatory Factor Analysis exhibited solid goodness of fit between SOCA items and the factor structure hypothesized in previous literature. Evidence of divergent validity shows SOCA differentiates the state anxiety and trait anxiety as expected. Limitations and possible topics for future research are also discussed.